2013
DOI: 10.1038/ncomms3662
|View full text |Cite
|
Sign up to set email alerts
|

Sequestration of Martian CO2 by mineral carbonation

Abstract: Carbonation is the water-mediated replacement of silicate minerals, such as olivine, by carbonate, and is commonplace in the Earth’s crust. This reaction can remove significant quantities of CO2 from the atmosphere and store it over geological timescales. Here we present the first direct evidence for CO2 sequestration and storage on Mars by mineral carbonation. Electron beam imaging and analysis show that olivine and a plagioclase feldspar-rich mesostasis in the Lafayette meteorite have been replaced by carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(93 citation statements)
references
References 36 publications
6
85
0
Order By: Relevance
“…The presence of secondary minerals within the mesostasis gives it a light brown colour when viewed using plane polarised transmitted light. Meunier et al (2012) interpreted the phyllosilicate-rich mesostasis to be a precipitate from late-stage magmatic fluids, whereas Tomkinson et al (2013a) concluded that phyllosilicate and siderite had formed by the water-mediated replacement of plagioclase feldspar.…”
Section: Mineralogy Of Lafayettementioning
confidence: 97%
See 2 more Smart Citations
“…The presence of secondary minerals within the mesostasis gives it a light brown colour when viewed using plane polarised transmitted light. Meunier et al (2012) interpreted the phyllosilicate-rich mesostasis to be a precipitate from late-stage magmatic fluids, whereas Tomkinson et al (2013a) concluded that phyllosilicate and siderite had formed by the water-mediated replacement of plagioclase feldspar.…”
Section: Mineralogy Of Lafayettementioning
confidence: 97%
“…Areas of mesostasis are $100 to 600 lm across (Fig. 1a) and are dominated either by plagioclase feldspar (Ab 62.6 An 31.8 Or 5.6 ; Bunch and Reid, 1975; Table 1) or phyllosilicate that is often intergrown with siderite (Tomkinson et al, 2013a). The presence of secondary minerals within the mesostasis gives it a light brown colour when viewed using plane polarised transmitted light.…”
Section: Mineralogy Of Lafayettementioning
confidence: 98%
See 1 more Smart Citation
“…Tomkinson et al [40] showed that olivine and a plagioclase feldspar-rich mesostasis in the meteorite have been replaced by carbonate over geological timescales. The susceptibility of olivine to replacement was enhanced by the presence of smectite veins along which CO 2 -rich fluids gained access to grain interiors.…”
Section: +mentioning
confidence: 98%
“…The example used in the discussion by Edwards and Ehlmann of the possibility of deep diffuse carbonate alteration-rather than precipitation of carbonate in discrete rock deposits like those analyzedwas selected based on measurements of carbonate in dust, in-situ mission data, and meteorites. That is, a 1 km global crustal layer of 1 vol.% carbonate-bearing materials, similar to the abundances in the Nakhaliteclass Lafayette meteorite (Changela and Bridges, 2010;Nyquist et al, 2001;Tomkinson et al, 2013;Wright et al, 1992), if formed from waters in contact with the atmosphere, would lead to sequestration of ~500 mbar CO 2 .…”
mentioning
confidence: 99%